2013
DOI: 10.1111/jce.12098
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Atrial Electrophysiological Properties Between Vagal and Sympathetic Types of Atrial Fibrillation

Abstract: There are better electrical properties and a smaller LA volume in patients with vagal-type AF. In contrast, the LA substrate is worse, and coexisting non-PV triggers and recurrence following ablation are more prevalent in patients with the sympathetic-type AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
1
14
1
Order By: Relevance
“…[12][13][14][15][16][17][18] Furthermore, it is known that non-PV triggers are associated with a larger LA and worse LA substrate. 24,25 This is confirmed by our study: at baseline, larger LA and scar were more prevalent in patients with LVSD than those of patients without LVSD.…”
Section: Importance Of Non-pulmonary Vein Foci In Paroxysmal Af Patiesupporting
confidence: 91%
“…[12][13][14][15][16][17][18] Furthermore, it is known that non-PV triggers are associated with a larger LA and worse LA substrate. 24,25 This is confirmed by our study: at baseline, larger LA and scar were more prevalent in patients with LVSD than those of patients without LVSD.…”
Section: Importance Of Non-pulmonary Vein Foci In Paroxysmal Af Patiesupporting
confidence: 91%
“…It is known that non-PV foci are associated with a large atrium and worse atrial substrate. 20, 22 In the present study, there was a tendency toward larger LA dimension in SSS patients than in those without SSS. Although we did not evaluate atrial voltage or scarring, Akoum et al reported that significant atrial fibrosis in the right atrium (RA) and LA quantified using late gadolinium enhancement-magnetic resonance imaging (LGE-MRI) is associated with clinically significant SSS.…”
Section: High Morbidity Of Non-pv Foci and Remodeling In Sss Af Patientsmentioning
confidence: 54%
“…While PV isolation remains the cornerstone of AF ablation, several studies have demonstrated that non-pulmonary vein foci also play an important role in initiation, maintenance and recurrence of AF [51-55]. Non-PV triggers are particularly important in patients with more longstanding AF, enlarged left atria and underlying heart disease, including HF [56]. Several studies have shown that ablation also of non-PV triggers, in addition to pulmonary vein isolation, improves arrhythmia free outcomes [57][58][59][60].…”
Section: Atrial Fibrillationmentioning
confidence: 99%